Nueva extensión del ámbito de Pontodrilus litoralis (Grube) (Oligochaeta: Acanthodrilidae) para el Pacífico Americano - Cantú-Martínez, Pedro César (1987)
Pontodrilus litoralis (Grube, 1855) is reported for the first time from beaches, salt-marshes and estuaries of Baja California and Oaxaca, in México. Its known distribution is extended with new limits for the American Pacific, from the coast of California, United States to the littorals of Oaxaca, México.